The Effect of a Proposed Training Program Using Functional Training Exercises on the Development of Some Physical, Skill, and Cardiac Functional Abilities: In Youth Basketball Players Aged (17–18) Years - Aladdin Abdullah Taha Abdullah Al-Muazani (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
This study aimed to examine the effect of a proposed training curriculum using functional training exercises on developing selected physical, skill, and cardiovascular functional abilities in basketball players aged 17–18 years. The sample consisted of 15 club players following the 2023/2024 season. An exploratory experiment was conducted on 5 players to establish the scientific basis of the tests, while the main experiment involved 10 players using a one-group experimental design with pre- and post-tests. The researcher designed and implemented a functional training-based curriculum tailored to the experimental group. Results showed significant improvements in all studied variables in favor of the post-test. Physical abilities improved notably, with arm speed-strength increasing by 35.45% and leg speed-strength by 43.84%. Skill performance also showed progress, with chest pass improving by 41.44% and layup shooting by 47.09%. In terms of cardiovascular function, heart rate (H.R.) improved by 24.50%, and stroke volume (S.V.) increased by 27.69%. These findings indicate that functional training exercises effectively enhance physical fitness, basketball skills, and cardiovascular efficiency in young players.